Species and abundance of ectoparasitic flies (Diptera) in pied flycatcher nests in Fennoscandia. Issue 1 (December 2015) - Eeva, Tapio; Andersson, Tommi; Berglund, Åsa; Brommer, Jon; Hyvönen, Raimo; Klemola, Tero; Laaksonen, Toni; Loukola, Olli; Morosinotto, Chiara; Rainio, Kalle; Sirkiä, Päivi; Vesterinen, Eero
Abstract Background Birds host several ectoparasitic fly species with negative effects on nestling health and reproductive output, and with the capability of transmitting avian blood parasites. Information on the abundance and distribution of the ectoparasitic fly generaOrnithomya (Hippoboscidae) andProtocalliphora (Calliphoridae) in northern Europe is still generally poor, and we thus explored their geographic range and occurrence of these flies in the nests of a common avian model species, the pied flycatcherFicedula hypoleuca . Methods Nests ofF. hypoleuca were collected from 21 locations across Fennoscandia in summer 2013, across a latitudinal gradient (between 56 °N – 70 °N) and examined for the presence of fly puparia. Adult specimens ofOrnithomya spp. were also collected for species identification. Fly species were identified morphologically and identifications confirmed with DNA barcoding. Results We found three species: two louse-flies −Ornithomya chloropus andO. avicularia − and one blow-fly, Protocalliphora azurea . The prevalence ofO. avicularia was higher in southern latitudes and this species was not encountered beyond 62 °N whereasO. chloropus andP. azurea occurred across the whole range of latitudes. The prevalence ofO. chloropus further increased with increasing distance from the coast – a pattern not documented before. The three fly species showed no interspecific associations in their prevalence. Conclusions Our study revealed relatively high prevalence for all the species (O. chloropus 59 %, O. avicularia 20 %, P. azurea 32 %), and an interesting spatial pattern in the prevalence of the two louse fly species. Our sample did not indicate any major range shifts towards the north for the southern species as compared to the information from the past. Morphological identification ofO. chloropus did not match with the corresponding sequences published in the GenBank and taxonomy of this group calls for further studies.